Approaches to fully documented fisheries: practical issues and stakeholder perceptions. Issue 3 (29th November 2013) - Mangi, Stephen C; Dolder, Paul J; Catchpole, Thomas L; Rodmell, Dale; de Rozarieux, Nathan
Abstract The Common Fisheries Policy (CFP) reform sets out a move to a land‐all catch policy in European Union waters with a requirement for full reporting of fishing and on‐board processing activity. We explore the merits, stakeholder perceptions and applicability of different technology and approaches to the full documentation of fisheries that might be considered in the context of implementing the CFP reform. While recent efforts have focused on demonstrating how remote electronic monitoring (REM) systems can be utilized in fully documented fisheries (FDF), other technologies and approaches such as reference fleet and self‐sampling exist that could contribute to delivering FDF. Perceptions of fishers show that they would prefer using a reference fleet or self‐sampling to REM systems as a future method of implementing FDF. In general, there is support from the fishing industry for data collection and enhancement, but there remains some mistrust concerning the use of the data. Findings show that the most appropriate means and methods of FDF will depend on the circumstances and objectives for full documentation whether in enforcing a discard ban, documentation of total catch or data enhancement. We conclude that any technology or approach that will be used to deliver the monitoring requirements for FDF needs to make practical and commercial sense at the fishing vessel level.